1347 Body Composition at 32–36 Weeks Corrected Age in Infants Born Before 32 Weeks Gestation. (October 2012) - Cumin, MB; Donovan, T; Colditz, PB; Lingwood, BE
Abstract : Background: Preterm infants at term equivalent age are smaller than full term infants with a higher fat mass. The aim of this study was to determine if alterations in adiposity are already evident at 32–36 weeks corrected age (CA). Methods: Preterm babies (n=21) born before 32 weeks gestation were studied between 32 and 36 weeks CA using the PEAPOD Infant Body Composition System to assess % body fat. The data were compared with a second group of babies (n=17) born at 32–36 weeks gestation. Results: Mean % body fat at 32–36w CA in infants born < 32w was 14.1±5.8 (mean ± SD) and this was significantly higher than % body fat in infants born at 32–36 weeks (7.9±4.5, P<0.01). Mean % body fat at 32–36 weeks in infants born < 32w was also significantly higher than % fat at birth in infants born at term (10.1±4.1, P<0.05). % body fat in infants born < 32w was positively correlated (R=0.59, P<0.05) with post-natal age at measurement suggesting that longer periods of ex utero nutrition result in greater increases on % body fat. % body fat in infants born < 32w was also positively correlated with weight at the time of measurement (R=0.56, P<0.01) and there was a tendency for those babies who had gained weight most rapidly since birth to have higher % fat. Conclusion: % body fat in infants born < 32 weeks is elevated by 32–36 weeks CA.